Pemeriksaan MPN (Most Probable Number) Coliform dan Identifikasi Escherichia Coli pada Jamu Gendong Beras Kencur - Amelia Valentina Randi Saputro (Poltekkes Kemenkes Semarang, 2019)
Herbal medicine of kencur rice is a traditional drink that is still consumed by the community. The manufacturing process is still using manual and traditional equipment and the lack of attention to cleanliness has become one of the factors causing contamination of herbs with bacteria. Based on the Regulation of the Food and Drug Supervisory Agency of the Republic of Indonesia Number. HK.00.06.1.52.4011 of 2009 on Determination of Maximum Limit of Microbial and Chemical In Food Contamination, maximum limit of coliform bacteria contamination on herbal medicine is 20 MPN/ ml. The purpose of research is to know the contamination of Coliform bacteria and to identify Escherichia coli in herbs medicine kencur at Peterongan Market. Method of the research is a descriptive research with cross sectional approach. The number of samples are 4 herbs of kencur packet sold in Peterongan Market, and the inspection is done in duplo. The result of Coliform bacteria examination on the samples of herbal medicine of kencur 100% containing Coliform bacteria, and of the four samples, 75% samples were identified Escherichia coli, so herbs samples of kencur sold in the market Peterongan Semarang, contaminated by Coliform bacteria and Escherichia coli.